Solution thermodynamics and preferential solvation of triclocarban in {1,4-dioxane (1) + water (2)} mixtures at 298.15 K (2017)
The equilibrium solubility and preferential solvation of triclocarban in {1,4-dioxane (1) + water (2)} mixtures at 298.15 K was reported. Mole fraction solubility varies continuously from 2.85 × 10–9 in neat water to 2.39 × 10–3 in neat 1,4-dioxane. Solubility behaviour was adequately correlated by means of the Jouyban-Acree model. Based on the inverse Kirkwood-Buff integrals, preferential solvation parameters were calculated. Triclocarban is preferentially solvated by water in water-rich mixtures (0.00 < x1 < 0.18) and also in 1,4-dioxane-rich mixtures (0.78 < x1 < 1.00) but preferentially solvated by 1,4-dioxane in mixtures with similar solvent compositions.